2019
DOI: 10.1186/s13148-019-0745-7
|View full text |Cite
|
Sign up to set email alerts
|

Smoking index, lifestyle factors, and genomic instability assessed by single-cell gel electrophoresis: a cross-sectional study in subjects from Yucatan, Mexico

Abstract: BackgroundIt is widely accepted that genomic instability is associated with several mechanisms involving oxidative stress, which can increase the rate of DNA breaks. Such factors include smoking, impairments in body composition, an unhealthy lifestyle, and a hereditary history of cancer. The aim was to evaluate the degree of association of genomic instability in smokers and non-smokers, and how the risk could change depending on the lifestyle and other causes. For this purpose, a survey of tobacco consumption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…Considering all children together, the present study revealed that children aged 10–11 years old had significantly higher tail moment compared to children aged 7 to 9 years old (3.03 ± 0.62 vs. 2.84 ± 0.71). Several studies have reported an increased DNA damage by older age as assessed by the comet assay [ 62 , 63 ]; meanwhile there are studies that showed no effect of age on the extent of DNA damage [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering all children together, the present study revealed that children aged 10–11 years old had significantly higher tail moment compared to children aged 7 to 9 years old (3.03 ± 0.62 vs. 2.84 ± 0.71). Several studies have reported an increased DNA damage by older age as assessed by the comet assay [ 62 , 63 ]; meanwhile there are studies that showed no effect of age on the extent of DNA damage [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…A smoking index was used to measure long-term tobacco consumption for each subject in the smoker group, which was calculated by the formula: (Daily smoking amount/ 20) × Smoking time. 30 Heavy smoking was defined as a smoking index ≥20 pack-years. The differences of statistics were tested using Mann−Whitney U tests for continuous variables and Fisher's tests for categorical variables.…”
Section: Discussionmentioning
confidence: 99%
“…For both groups, descriptive statistics were used to demonstrate the basic and clinical characteristics of the study population. A smoking index was used to measure long-term tobacco consumption for each subject in the smoker group, which was calculated by the formula: (Daily smoking amount/20) × Smoking time . Heavy smoking was defined as a smoking index ≥20 pack-years.…”
Section: Methodsmentioning
confidence: 99%
“…Cabe señalar al respecto que, dentro de este grupo, las que tuvieron el DB-N elevado fueron mayores de 25 años, y además todas habían estado expuestas a tratamientos con QTP y/o RTP. Si consideramos que diferentes factores pueden contribuir al daño del ADN, el incremento en las roturas de doble hebra pudiera deberse al efecto combinado de la edad, el tratamiento antineoplásico que recibieron, y la presencia de alguna susceptibilidad individual no identificada, que no implica a los APF-C, además de la dieta, el estilo de vida, la exposición ambiental, el metabolismo celular (11,30,31).…”
Section: Discussionunclassified
“…Por otra parte, la que presentaba Rb-B no recibió QTP y/o RTP. Como ya se ha mencionado, factores como la dieta, el estilo de vida, la exposición ambiental, el metabolismo celular (11,30), podrían estar relacionados con el incremento del DB-N en ellas. A su vez, la presencia de una susceptibilidad genética individual, también ya sugerida (26,27), podría estar in uenciando el daño del ADN.…”
Section: Discussionunclassified